1991
DOI: 10.1159/000116755
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies on the Anti-Migraine Drug, Sumatriptan

Abstract: Sumatriptan is believed to constrict selectively the cranial vessels that are distended and inflamed during migraine. The action is mediated by activation of a 5-HT1 receptor subtype which has been shown in animals to be localized in cranial vessels. Further studies to elaborate sumatriptan’s precise clinical mode of action have focused on the human meningeal circulation and should lead to a better understanding of the pathogenesis of migraine. Administering [14C]sumatriptan, drug-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(84 citation statements)
references
References 0 publications
2
82
0
Order By: Relevance
“…But the relatively low brain penetration of sumatriptan called into question whether CNS effects were at all necessary for its antimigraine activity (Humphrey et al, 1991). Disruption of the blood-brain barrier by hyperosmolar mannitol infusion was used to study possible CNS actions of sumatriptan.…”
Section: Cns Mechanisms Of Tripan Actionmentioning
confidence: 99%
“…But the relatively low brain penetration of sumatriptan called into question whether CNS effects were at all necessary for its antimigraine activity (Humphrey et al, 1991). Disruption of the blood-brain barrier by hyperosmolar mannitol infusion was used to study possible CNS actions of sumatriptan.…”
Section: Cns Mechanisms Of Tripan Actionmentioning
confidence: 99%
“…It is virtually devoid of 5-HT2 and 5-HT3 activity [9]. Radioligand and binding studies [29] have shown it to have highest affinity for the 5-HTlD receptor subtypes and weaker affinity at the 5-HTlA subtype (pKD, 7.54 and 6.13, 5-HTID and 5-HTlA, respectively).…”
Section: Cortisolmentioning
confidence: 99%
“…Activation of pre-synaptic auto-inhibitory receptors at this site would reduce the release of CRF and hence ACTH. 5-HTID receptors have been demonstrated to occur in low levels in the hypothalamus [33], suggesting that this may be a possible site of action for sumatriptan, although studies in several species have shown that the passage of sumatriptan and its metabolites across the BBB is very limited [9,30].…”
Section: Cortisolmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] According to U.S. half-lives of the active ingredient. [10][11][12][13] Time periods between sampling mustn't exceed one terminal half-life. [14] From the pharmacokinetic data reported in the existing literature, it absolutely was found that the halflife (t1/2) of sumatriptan is close to 1 to 2 h. [15] Hence, in the present study, the samples were collected up to 12 h after drug administration as to cover a minimum of 3 half lives of the sumatriptan.…”
Section: Instrumentation and Chromatographic Conditionsmentioning
confidence: 99%